AQUA: Analytical model for evaluation and selection of Third-Party Logistics service provider in supply chain. (1st January 2011) - Rajesh, R.; Pugazhendhi, S.; Ganesh, K.; Muralidharan, C.
Selection of Third-Party Logistics (3PL) service provider is a strategic decision making in supply chain network. The challenge and need for supply chain analyst is to develop a real-life simple and implement-ease model, which can handle the voice of customer and internal and external business metrics for evaluation and selection of 3PL service provider. We develop a three-phase analytical model with the integration of Analytic Hierarchy Process (AHP) and Quality Function Deployment (QFD). In the current competitive scenario, the consideration of business metrics and voice of customer for evaluating the selection criteria of 3PL service provider benchmarks the agility of an organisation. The analytical model is validated and illustrated with a real-life case study.